Software Design Document (SDD) Manajemen Inventaris Aset Teknologi Informasi: Manajemen Inventaris Aset Teknologi Informasi - Rawung, Jemmi; Widyarto, Setyawan (Proceedings of the Informatics Conference, 2024)
Assets from the Information Technology (IT) department such as hardware or software are widely used by computer users who receive services from the IT department. Some issues occur related to these assets such as losing the information or even the existence of the asset is not known. Applications are one of the answers to record all the logs and store all information from the first time the asset was purchased until it was not used or had to be replaced with a new one. Here the application development will use the Python programming language to make it easier to find information and perform inventory management from IT assets and MySQL as a database.